NURSING CARE IN TN. S WITH HYPERTENSION THROUGH SLOW STROKE BACK MASSAGE THERAPY IN SUNGAI RANGAS ULU VILLAGE - Iswari, Dedi; Rizany, Ichsan (Nerspedia, 2023)
Background: Most people with hypertension are not aware of having hypertension or getting treatment. Hypertension that is nottreated properly can cause complications such as stroke, coronary heart disease, diabetes, kidney failure and blindness. Data fromthe UPT of the West Martapura Health Center in March 2022, hypertension was ranked first for non-communicable diseases. Oneof the non-pharmacological treatment therapies that can be used to reduce blood pressure in patients with hypertension is slowstroke back massage therapy. Purpose: To provide comprehensive nursing care with slow stroke back massage therapy to reduceblood pressure.